Malnutrition in elderly and its relation to depression - Al-Rasheed, Rana; Alrasheedi, Radiah; Al Johani, Razan; Alrashidi, Hamidah; Almaimany, Bayan; Alshalawi, Bandar; Kelantan, Abdulhfeez; Banjar, Ghadeer; Alzaher, Afaf; Alqadheb, Ahmad (International Journal Of Community Medicine And Public Health, 2018)
The notable increase in number of individuals reaching advancing ages over the past decades resulted in the emergence of various physical and mental disorders that necessitate intervention. Two of the major illnesses encountered at this age group include depression and malnutrition. Depression and malnutrition are prevalent among geriatric population and seem to be strongly associated. The relationship between those two conditions is interactive. Depression leads to appetite and weight changes that results in malnutrition, and poor nutrition predispose old individuals to psychiatric upset (depression, agitation, and irritability). Loss of appetite and weight and major criteria for diagnosis of depression. It is suggested that the neurotransmitters and hormonal changes occurring in depressing are responsible for alteration in appetite. On the other hand, dietary supplements are essential for mood regulation. Carbohydrates, proteins, vitamin B, selenium, zinc, lithium, chromium, calcium, and other trace elements are protective against depression. Depression and malnutrition have common risk factors such as loneliness, lack of social support, physical illness, functional impairment, financial paucity, and endocrinal disturbances. There is a vicious circle between depression and malnutrition. Therefore, clinicians should pay attention to both psychological and physical aspects during treating elderly with depression, malnutrition, or both. This article aims to discuss the relationship between depression and malnutrition among geriatric population.